pengaruh IPM, Gini Rasio dan Tingkat kemiskinan terhadap TPT di Kabupaten Aceh Singkil - Irmatriyanti Irmatriyanti; Windari Windari; Muhammad havis; Asnidar Asnidar; ahmad ridha (Akuntansi, 2023)
This study aims to determine and analyze the effect of the Human Development Index, Gini ratio, and poverty level on the open unemployment rate in Aceh Singkil Regency. The data used in this study come from secondary sources obtained from the Central Bureau of Statistics from 2014 to 2021. The data analysis method uses multiple linear regression using eviews10 software. The results of the study show that partially HDI has a positive and significant effect on the open unemployment rate in Aceh Singgkil Regency, the Gini ratio partially has a negative and insignificant effect on the open unemployment rate. And the poverty rate partially has a positive and insignificant effect on the open unemployment rate. And in this study HDI, Gini Ratio and Poverty Level simultaneously or together have a positive and significant effect on the open unemployment rate in Aceh Singkil Regency and show that these three variables contribute to the unemployment rate with a significant impact.